Prevalence of and risk factors for pulmonary abnormalities in HIV‐infected patients treated with antiretroviral therapy. Issue 6 (8th December 2013) - Sampériz, G; Guerrero, D; López, M; Valera, JL; Iglesias, A; Ríos, Á; Campins, A; Sala, E; Murillas, J; Togores, B; Palmer, J; Rodriguez, M; et al.
<x xml:space="preserve">Abstract</x> Background Pulmonary abnormalities are often present in patients infected with the human immunodeficiency virus (HIV). Objectives The aim of the study was to determine the prevalence and characteristics of, and risk factors for, pulmonary abnormalities in HIV‐positive patients. Methods A total of 275 HIV‐positive patients [mean (± standard deviation) age 48.5 ± 6.6 years] were included in the study, of whom 95.6% had been receiving highly active antiretroviral therapy (HAART) for a mean (± standard deviation) duration of 11.9 ± 5.4 years. The median (interquartile range) CD4 lymphocyte count was 541 (392–813) cells/μL, and 92% of the patients had an undetectable viral load. We determined: (1) spirometry, static lung volumes, lung diffusing capacity, pulmonary gas exchange and exercise tolerance, and (2) the amount of emphysema via a computed tomography (CT) scan. Results Chronic cough and expectoration (47%) and breathlessness during exercise (33.9%) were commonly reported. Airflow limitation (AL) was present in 17.2%, low pulmonary diffusing capacity in 52.2% and emphysema in 10.5−37.7% of patients, depending on the method used for quantification. Most of these abnormalities had not been diagnosed or treated previously. Smoking exposure and previous tuberculosis were the main risk factors for AL, whereas smoking exposure and several variables related to HIV infection appeared to contribute to the risk of emphysema and low diffusing capacity. Conclusions Despite HAART, pulmonary structural and functional abnormalities are frequent in HIV‐positive patients. They are probably attributable to both environmental (smoking and tuberculosis) and HIV‐related factors. Most of these abnormalities remain unnoticed and untreated. Given the relatively young age of these patients, these results anticipate a significant health problem in the next few years as, thanks to the efficacy of HAART, patients survive longer and experience the effects of aging.